A retrospective study: Impact of consensus treatment plans on systemic therapy of pediatric morphea. Issue 2 (22nd January 2020) - Do, Ngan; Ringold, Sarah; Sullivan, Erin; Brandling‐Bennett, Heather
Abstract: Background: Morphea is an inflammatory and fibrosing condition that affects the skin and subcutaneous structures. Morphea is managed by dermatologists, rheumatologists, or both. Prior studies have suggested there is significant variability in approach to treatment. In 2012, the Childhood Arthritis and Rheumatology Research Alliance (CARRA) published consensus treatment plans (CTPs) for pediatric morphea to develop more standardized treatment plans for patients requiring systemic therapy. We aimed to assess whether the publication of CTPs has impacted care of patients with morphea at our institution. Methods: Data were collected via a retrospective review of medical records of 61 pediatric patients diagnosed with morphea at Seattle Children's Hospital (SCH) from January 1, 2005, to December 12, 2017. Results: Prior to the publication of CTPs, 2 out of 24 patients (8.3%) were treated with a regimen that matched a subsequent CTP. After publication of CTPs, 29 out of 37 patients (78.4%) were treated with a regimen that matched a CTP ( P < 0.001). A subanalysis was performed to assess the number of patients who needed second‐ or third‐line therapies. Of those who followed a CTP therapy plan (n = 26), 3 patients (11.5%) needed a second‐line therapy compared with 11 patients (44%) in the no‐CTP followed group (n = 25), ( P = 0.012). Conclusions: The publication of CTPs led to a significant change in treatment approach for patients with morphea requiring systemic therapy at SCH. Patients treated with one of the treatment plans recommended by the CTPs were less likely to need second‐line systemic therapy.